The letters between Ricardo Palma and Rafael Altamira in the context of 98 - Valero Juan, Eva (2023)
The letters between Ricardo Palma and Rafael Altamira, some of them published in the General Epistolary of the traditionist by the Ricardo Palma University, and others in the Miguel de Cervantes Virtual Library (the last one coming from the Altamira legacy deposited in the Secondary Education Institute Jorge Juan de Alicante) are a first-rate source for research on cultural relations between the two intellectuals. This relationship is paradigmatic of the reestablishment of the bridges of communication brought about by the events of ‘98, in the context of the controversy between Latins and Anglo-Saxons that marked the inter-century period. The letters analyzed in this paper, which cover the period from 1895 to 1910, open a new angle for the analysis of this crucial period in the history of cultural relations between Spain and Latin America since the beginning of the 20th century. Keywords: Ricardo Palma, Rafael Altamira, letters, intellectual and cultural affinity.